PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hasmirati Hasmirati; Alfin Akuba (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2019)
The object of this research is the manufacturing companies listed on the Indonesia Stock Exchange. The analytical method used in this study is descriptive analysis using multiple linear regression where the data obtained from the Indonesia Stock Exchange. The results obtained in this study are simultaneous current ratios, and the debt to equity ratio has a significant effect on return on assets. Partially the current ratio has a negative and significant effect on return on assets, while the debt to equity ratio has a positive and significant effect on return on assets.